Dinamika Bursa Saham Asing dan Makroekonomi terhadap Indeks Harga Saham Gabungan Bursa Efek Indonesia - Rowland Bismark Fernando Pasaribu; Dionysia Kowanda (Jurnal Akuntansi dan Bisnis, 2013)
The development of the interaction of monetary indicators, foreign stocks, and the stock price index in the context of the dynamics of the relationship are discussed short and long term. The analysis technique used is cointegration analysis and error correction mechanisms for the period 2003-2010. From the research results that: a) in the short term, rising inflation will lead to decline in the stock price index, but in the long run, instead of rising inflation, ceteris paribus, it will increase the stock price index. Partially, the inflation rate did not significantly influence the stock price index in both the short-and long-term, b) 3-month SBI rate negative, but not significant effect on the stock price index in both the short and long term, c) increase in the number of money supply in the short term, will increase the stock price index, both in short and long term; d) the exchange value of rupiah against the U.S. dollar has significant negative effect on stock price index, both short and long term; e) reserves countries have positive and significant impact on the stock price index in both the short-and long-term; f) for foreign exchange, short-term period, the increase in the composite index of stock markets of Malaysia and Singapore ceteris paribus, it will reduce Indonesia's stock index, while for two other exchanges, PSEI and Shanghai, have positive implications of IDX fluctuations. Fluctuations in both the exchange of each will improve the IDX Composite Index. In the long term, unless the Singapore stock market, fluctuations in the three stock exchanges will improve IDX; g) simultaneously, the monetary indicators and the foreign exchanges have positive and significant impact on the stock price index, both short term and long term.